Contribuição ao estudo de reações mediadas por calcogenetos Zn e Cu: hidrocalcogenação de ácidos e ésteres e síntese de sulfetos arílicos - Nunes, Vanessa Loren (2012)
This work describes some studies on the preparation of unsymmetrical diaryl thioethers catalyzed by Copper(I)-Senelenophene-2-carboxylate. The results concern to the catalyzed cross-coupling reaction between aryl halides and aryl or alkylthiols using Copper(I)-Senelenophene-2-carboxylate (CuSC) a new Cu-catalyzed one-pot protocol. The products were obtained in good to excellent yields under relatively mild reaction conditions presenting chemoselectivity and functional group tolerance. Additionally, we have developed a chemio-, regio and stereoselective synthesis of vinyl chalcogenides compounds promoted by zinc chalcogenolates. In this protocol the reductive cleavage of chalcogen bond by the Zn/NH4OH system led to zinc chalcogenolates. The reaction was carried out with acids and esters propiolics afford β-chalcogenacrillic acids and esters under mild and basic conditions. The stereochemistry corresponding to anti-Markovnikov addition of the chalcogenolate constituents across the triple bond were obtained in good yields.